Preparation and electrochemical performances of Ni-rich LiNi0.91Co0.06Mn0.03O2 cathode for high-energy LIBs. (21st May 2019) - Lee, Seung-Hwan; Lee, Seul; Jin, Bong-Soo; Kim, Hyun-Soo
Abstract: One important challenge of lithium ion batteries is to improve the energy density while maintaining long-term cyclability. The energy density is strongly dependent on the Ni content in LiNi1-x-y Cox Mny O2 . Herein, Ni-rich LiNi0.91 Co0.06 Mn0.03 O2 has been synthesized as a high energy cathode material by co-precipitation method and the electrochemical performance of the LiNi0.91 Co0.06 Mn0.03 O2 has been investigated. The granule morphology LiNi0.91 Co0.06 Mn0.03 O2 with high crystallinity is obtained and which delivers a discharge capacity of 208.3 mA h g −1 with cyclability of 61.9%, after 100 cycles and rate performance of 85.6%, at 2 C. These findings indicate that LiNi0.91 Co0.06 Mn0.03 O2 is one of the promising candidate cathode for high-energy lithium ion batteries. Highlights: NCM91 was prepared with high crystallinity. NCM91 has a discharge capacity of 208.3 mA h g −1 . NCM91 shows a rate capability of 85.6%, at 2 C. NCM91 shows a stable cyclability of 61.9%, after 100 cycles.